دراسة تحليلية لفجوة التوقعات ببيئة المراجعة الخارجية للحسابات في الجزائر - سردوك, فاتح (جامعة الوادي University of Eloued, 2015)
تهدف هذه الدراسة إلى رصد وتحليل مكونات فجوة التوقعات للمراجعة الخارجية للحسابات، والتي تعتبر مشكلة معاصرة عامة لا يمكن استثناء أي بيئة مراجعة منها، وهذا إسقاطا على بيئة الممارسة المهنية للمراجعة الخارجية للحسابات في الجزائر، من خلال الوقوف على مهام ومسؤوليات المراجع الخارجي للحسابات في الجزائر، من وجهة نظر المراجعين الخارجيين، وما ينتظره منهم المجتمع المالي من جميع الفئات المستفيدة من خدمات المراجعة الخارجية، والتي تتمثل في المهام والمسؤوليات والخدمات المنتظرة من المراجعين في ظل ما يحكم مهنة المراجعة من تشريعات وطنية، وتوافقا مع المعايير الدولية للمراجعة وهذا لغياب كلي لمعايير وطنية للمراجعة، مما يتيح لنا رصد فجوة التوقعات للمراجعة الخارجية للحسابات بالجزائر وتحليل مكوناتها. Abstract : This study aims to follow and analyze the components of the expectation gap of external audit in Algeria. Which are a contemporary general problem that we cannot exclude from any audit environment, according to the environment of the professional practice of external audit in Algeria. Relative to the point view of external auditors to the functions and responsibilities of external audit in Algeria, and the viewpoint and what expects the financial community. With all its categories, that benefits of external audit services, which consist of tasks and responsibilities expected of the auditors services required to what governs the auditing profession by national legislation, and in accordance with international standards of audit. In light of the total absence of national audit standards, allowing us to follow the audit expectation gap in Algeria and analyze its components. Keywords: expectation gap, external audit, Auditor responsibilities, Auditor Tasks, expectations of the financial community.
Analytical study of the expectation gap in the environment Of external audit in Algeria
مقال- مجلة رؤى اقتصادية
Keywords: فجوة التوقعات، المراجعة الخارجية للحسابات، مسؤوليات المراجع، مهام المراجع، توقعات المجتمع المالي; expectation gap, external audit, Auditor responsibilities, Auditor Tasks, expectations of the financial community.